How Financial Literacy Influences the Lifestyle of Generation Z and Individual Consumption Behaviour in Indonesia: A Case Study of Users of Organic Skincare Products - Annisa Salsabilla; Sita Deliyana Firmialy (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract This study aims to determine the influence of financial literacy and lifestyle skills on the consumption behavior of organic skincare users among generation Z. Quantitative research employing a descriptive and causal approach is employed as the method of investigation. This study's sample consists of users of organic skincare products who are members of generation Z or fall within the age range of 10 to 26 years. The sampling strategy for this investigation will be determined using a purposive sample. The questionnaire results were then analysed using the structural equation modelling-partial least square (SEM-PLS) method, with 121 respondents comprising the sample. The findings of this study indicate that financial literacy significantly influences consumption behaviour, lifestyle significantly influences consumption behaviour, and lifestyle significantly influences financial literacy. Furthermore, the findings demonstrate that financial literacy can significantly moderate the impact of lifestyle on purchasing habits. Keywords: Financial Literacy, Lifestyle, Consumption Behavior Abstrak Penelitian ini bertujuan untuk mengetahui besarnya pengaruh yang diberikan kemampuan financial literacy dan lifestyle terhadap consumption behavior pengguna skincare organic pada kalangan generasi Z. Metode penelitian yang digunakan yaitu penelitian kuantitatif dengan pendekatan deskriptif dan kausalitas. Populasi untuk penelitian ini yaitu pengguna skincare organic yang termasuk pada kalangan generasi Z atau pada rentang usia 10 – 26 tahun. Pada penelitian ini dalam penentuan pengambilan sampel akan menggunakan teknik purposive sampling.1Hasil kuesioner kemudian dianalisis dengan teknik Structural Equation Modeling-Partial Least Square (SEM-PLS), dengan hasil sampel yang digunakan sebanyak 121 responden. Hasil penelitian ini menunjukan adanya pengaruh secara signifikan dari financial literacy terhadap consumption behavior, lifestyle terhadap consumption behavior, dan lifestyle terhadap financial literacy. Selain itu, didapatkan hasil bahwa financial literacy secara signifikan dapat menjadi mediasi pengaruh antara lifestyle terhadap consumption behavior. Kata Kunci: Literasi Keuangan, Gaya Hidup, Perilaku Konsumsi